The catalytic efficiency of Lipin 1beta increases by physically interacting with the protooncoprotein c-Fos - Cardozo Gizzi, Andres Mauricio (2015)
Phosphatidic acid (PA) is a central precursor for membrane phospholipid biosynthesis. Lipin family is a Mg-dependent type I PA phosphatase,involved in de novo synthesis of neutral lipids and of phospholipids. The regulation of Lipin activity may govern the pathways by which these lipids aresynthesized and control the cellular levels ofimportant signaling lipids. On the other hand, the proto-oncoprotein c-Fos has an emerging role in glycerolipid synthesis regulation: by interacting with key synthetizing enzymes it is able toincrease overall phopho- and glyco- lipid synthesis.We studied the Lipin 1β enzyme activity in a cell-free system using PA/Triton X-100 mixed micelles as substrate, analyzing it in the presence/absence of c-Fos. We found that Lipin 1β kcat increases around 40% in the presence of c- Fos, with no change in the Lipin 1β affinity for the PA/Triton X-100 mixed micelles. We also probed a physical interaction between both proteins. While the c-Fos domain involved in Lipin activation is its basic domain (BD), the interaction domain is mapped to the c-Fos N-terminal. In conclusion, we provide evidence for a novel positive regulator of Lipin 1β PA phosphatase activity that is not achieved via altering its subcellular localization or affinity for membranesbut rather through directly increasing its catalytic efficiency.